Optimization of optical modulator chirp measurement technique using differential frequency beating - Abdul Rashid, Hairul Azhar; Al-Qdah, Malik T.; Chuah, Hean Teik; Tayahi, M. B.; Abdullah, Mohammad Khazani (Wiley Periodicals, 2007)
Optimization of the optical modulator chirp measurement technique using differential frequency beating is presented in this paper. The performance of the chirp measurement technique is studied ht terms of the measurement range, sensitivity, and resonant frequency as the accumulated chromatic dispersion (CD) in the fiber is varied. Based on the mathematical model and experimental and simulation results, the technique's measurement range and sensitivity increase with reduced accumulated CD in the fiber. However, the resonant frequencies increase with reduced accumulated CD. The chirp measurement technique is optimized at an accumulated CD of similar to 600 ps/nm, with a measurement range of +/- 4.75, maximum sensitivity of 3.3 GHz, and maximum resonant frequency of 14.28 GHz. (C) 2007 Wiley Periodicals, Inc.